Ecology and Environmental Challenges of the Persian Gulf. Issue 6 (1st November 2016) - Bayani, Niloufar
Abstract : The extreme salinity and temperature fluctuations of the Persian Gulf waters have created unique marine and coastal ecosystems, with numerous benefits to Iran and neighboring countries. However, human activities, including rapid coastal development, land-based pollution, oil and gas extraction, and shipping, are threatening the survival of these ecosystems. With long shorelines, a large coastal population, and locally important fisheries and tourism-related jobs, Iran has a lot at stake in the degradation of its marine and coastal environments. However, it is not too late to put a stop to further degradation. This article recommends a number of targeted actions at the local, national, and regional levels to address the threats to the Persian Gulf 's environment and protect this important renewable resource.